Zapletene poškodbe žilja spodnjih udov pri otrocih - Flis, Vojko (Zdravniški vestnik, 2007)
Background. Pediatric vascular trauma is rare and there is scarcity of data available to direct optimal care of these patients. Even rarer are reports of long term venous function after complex vascular repairs of lower extremities. Purpose of articl is to evaluate the long term arterial and venous function after complex vascular repairs with interposition vein graft, vein by-pass graft or moditified veno-venous saphenous ven by-pass graft. A prospective cohort study of children with combined lower extremity vessel injuries (arterial and venous) treated during 10-year period (1995-2005). All patients were followed up in regular six months intervals by color flow duplex ultrasound imaging. Six months after injury radioisotopic phlebography was performed. In selected cases arteriography was performed and isotopic phlebography repeated. Patients. Seventeen patients (range 3-16 years, 15 male) were followed up (range 6 months - 10 years) after complex trauma of lower extremities (traffic-related injuries 15 cases, farming machines-related injuries 2 cases). By all patients there were associated injury of bone structures and other associated injuries. There were 10 patients with extensive laceration of superfacial femoral artery and vein. Both vessels were reconstructed with an interposition vein graft (great saphenous vein). There were 7 patients with extensive popliteal artery and vein laceration and associated injuries to crural vessels. Vessels were reconstructed (arterial part) with reversed vein by-passes (there cases of additional popliteo-pedal by-pass) and with veno-venous saphenous vein by-pass (venous part) with H interponat. Results. All repairs were patent, with no evidence of deep venous thrombosis. There were no signs of chronic venous insufficiency. By three patients with veno-venous by-pass varicose veins developed. There were no disturbances in limb growth. Conclusions. Long term potency of venous repair in presented group of patients is excellent. Complex venous were repairs in this particular group in majority of patients not associated with functional changes consistent with chronic venous insufficiency.
Keywords: Angiografija; Angiography; Arteries; Arterije; Child; injuries; Kirurški postopki, operativni; kirurško zdravljenje; Lower Extremity; otroci; Otrok; ožilje; Poškodbe; Spodnja ekstremiteta; Surgical Procedures, Operative; Veins; Vene; žile